Microstructure of CEM II/B-S Pastes Modified with Set Accelerating Admixtures - Jan Pizoń (MDPI AG, 2021)
The presented paper aims to describe the influence of accelerating admixtures on the properties and microstructure of cement pastes and mortars. Blended slag cement CEM II/B-S containing two different clinkers (differing amounts of siliceous and aluminous phases) and four types of accelerators (calcium nitrate, sodium hydroxide, cement kiln dust, and crystal seeds) were used in research. Compressive strength tests (after 12, 24, 48 h of curing), Scanning Electron Microscope (SEM) observations together with an Energy Dispersive Spectroscopy (EDS) analysis, Mercury Intrusion Porosimetry (MIP) tests, and X-ray diffraction (XRD) analysis were conducted. Results have shown that SEM and EDS examination of the microstructure of cement pastes modified with accelerating admixtures at the observed points did not reveal differences that would be sufficient to explain the changes in compressive strength. Still, the increase in amorphous phase content indicates a faster hydration reaction rate for all pastes modified with accelerating admixture. It is backed up also by lower non-hydrated compounds content. All admixtures accelerate the hydration reaction of calcium silicate phases of cement, but only NaOH and cement kiln dust (CKD) influence the aluminate phase reaction rate. The pore volume is independent of the clinker type, while the pore size distribution is not.